백서의 아킬레스 건 봉합 후 Hyaluronate-Carboxymethyl cellulose가 조직 유착에 미치는 영향 - 이정희; 정비오; 김교영; Lee, Jung-Hee; Jeong, Bi-O; Kim, Gou-Young (대한족부족관절학회지, 2009)
Purpose: The purpose of this study was to evaluate the effect of Sodium hyaluronate-Sodium carboxymethyl cellulose (HA-CMC) on tissue adhesion after tenorrhapy in tenotomized Achilles tendon of the Sprague-Dawley rat. Materials and Methods: Twenty-eight legs of 14 Sprague-Dawley rat were used in study. After tenotomy of the Achilles tendons, tenorrhaphies were performed. Simple tenorrhaphy without any other procedures were performed on the left Achilles tendons (control group), and additional HA-CMC injections were done prior to the tenorrhaphy on the right Achilles tendons (HA-CMC group). Gross and histological examinations were made to identify differences between the two groups, 1, 2, 6, 8, 10, 12 and 14 weeks respectively. Results: Distinct decrease in granulation tissues and adhesions were seen in the HA-CMC group during gross inspection at 6 and 8 week after the operation. On histological analysis of the HA-CMC group, although increased infiltrations of inflammation cells were observed during 1 week, less adhesion were seen at 6, 8 and 10 weeks after the operation. In HA-CMC group, superior healing processes were seen at 6, 8 and 10 weeks and less fibrotic changes, compared to control group, were seen at 2 and 6 weeks. Conclusion: Prevention of adjacent tissue adhesion was made possible through decrease in collagen deposition and fibrosis by injecting HA-CMC before tenorrhaphy of Achilles tendon. Also, histologically faster healing process of the collagen fibers within the Achilles tendon was observed.